THE ROLE OF SUSTAINABLE CROP PRODUCTION AND PROTECTION SYSTEMS IN REDUCE THE RATE OF PLANT DISEASE EPIDEMIOLOGY: PERAN SISTEM PRODUKSI DAN PERLINDUNGAN TANAMAN YANG BERKELANJUTAN DALAM MENEKAN LAJU EPIDEMIOLOGI PENYAKIT TANAMAN - yolanda, Cindy (UPMI Proceeding Series, 2023)
This research is a literature study with a type of descriptive qualitative research with a literature review (Library research) that describes the epidemiological challenges of plant diseases in food security. The author uses various written sources such as articles, journals and documents relevant to the study in this study. In order to increase the role of the agricultural sector, the development of a sustainable food system is a key requirement. Factors that support modern agriculture are human resources (HR), high-quality seeds, quality agricultural products, and high-tech mechanization. The components that become anticipatory steps in suppressing the rate of plant disease epidemics, including: determination of planting location and time, planting resistant varieties, planting healthy seeds, fertilization, physical and mechanical control, chemical control and biological control.